A History of the Temple of the Emerald Buddha - Subhadradis Diskul M.C. ([Bangkok, Thailand] Bureau of the Royal Household, 1982)
On the Buddhist temple which is built in 1782 in Bangkok, Thailand.
Keywords: Temple of the Emerald Buddha; Buddhist shrines -- Thailand -- History; Buddhist temples -- Thailand -- History; Shrines -- Thailand -- History